Diagnostic Reliability of In-Person Versus Remote Dermatology: A Meta-Analysis - Bastola, Mrigendra (Telemed J E Health, 2021)
Background: Studies comparing teledermatology with in-person dermatologists report wide variations in diagnostic agreement. Teledermatology studies should have two independent in-person consultations establishing a baseline for comparing diagnoses made face-to-face and those made remotely. Objective: To perform a meta-analysis of comparison studies having two in-person dermatologists and at least one remote dermatologist examining the same patients to determine the overall preponderance of agreement. Method: Studies having two in-person diagnosticians were identified from previous teledermatology research reviews and independent searches of PubMed and other databases. Data from six studies identified were meta-analyzed. Results: Some studies showed high levels of diagnostic concordance, while others did not. Meta-analysis revealed that concordance rates reported in the teledermatology and clinical (in-person) consultations were significantly different (odds ratio = 0.55 [Mantel–Haenszel, fixed effect model, 95% confidence interval = 0.42–0.72], χ(2) = 11.87, p < 0.05, I(2) = 58%). Overall results showed that in-person primary diagnoses are significantly more concordant than remote. The results also suggest that diagnoses made in-person and teledermatology were marginally but significantly different than remote. Conclusion: Although the results of this study suggest teledermatology diagnoses are less reliable than those in-person, there are still valid reasons for using teledermatology to improve access, reduce costs, and triage patients to determine those warranting further in-person consultation and/or laboratory tests. More caution should be exercised in teledermatology when diagnoses involve risky skin conditions. There is evidence that this happens in practice.